The Non-Suspensive Effect of the Appeal for Annulment and the Exception Thereto in UAE Legislation: A Comparative Study - Al Qadi, Youssef; Al Abdouli, Iman (Journal of Legal Sciences, 2026)
To achieve the principle of legality, the Emirati legislator decided that administrative decisions are subject to judicial oversight, where all civil and administrative legal actions are subject to the supervision of the unified judiciary. The Federal Supreme Court affirmed that filing an annulment lawsuit does not result in the suspension of the contested decision, as stated in its rulings: 'The filing of a lawsuit to annul an administrative decision, as a general principle, does not lead to the suspension of the implementation of the administrative decision. Conversely, the execution of the decision and the utilization of its subject matter do not prevent the continuation of the consideration of the annulment request and the ruling on its subject, as the lawsuit aims to ensure the legality of the decision and its compliance with the established principles in the law.'The principle of non-retroactivity has decided on annulment because it serves the public interest, since administrative actions are presumed to require urgency and necessity in order to achieve their objectives. Therefore, it is essential that no individual, regardless of who they are, is allowed to halt its progress or stop its activity simply by filing for annulment.